Making history in Banda : anthropological visions of Africa's past - Stahl, Ann Brower, 1954- (New studies in archaeology., 2001)
Using approaches from several disciplines, Stahl reconstructs the daily lives of Banda villagers of west central Ghana, from when they were drawn into the Niger trade (around 1300 AD) until the twentieth century establishment of British overrule. Stahl argues for closer integration of archaeology, history and anthropology in African studies.